Microorganismos degradadores de gasolina e óleo diesel isolados de solos do Amazonas - Mari, Alessandra de Oliveira (2008)
Petroleum industries sector is one of the most that provoke environmental impact, due to their volume and recalcitrant compounds. The hydrocarbonates remotion from contaminated soil is an essential practice for environmental interests. There are various methods to minimize the negative effects of the soil contamination. A strategy for the petroleum elimination and its subproducts from contaminated soils is trough the bioremediation, which is the utilization of process or biological activities to transform contaminants in inert substances. Four rhizospheric soils from native forest were collected from the Base de Operação Geólogo Pedro de Moura , Urucu, Coari, and four rhizospheric soils from fruit species (cupuassu, graviola, camu-camu and arassa-boi) from the Rural Community of Brasileirinho, Manaus, during may 2007, to evaluate the presence and isolation of microbial culture with potential for gasoline and oil diesel degradation. All soil rhizosphere samples presented microorganisms able to use gasoline and oil as carbon sources. The addition of gasoline or diesel oil to the soil samples of native forest and fruit species resulted on substantial increases of the microorganisms population. The soil rhizosphere samples from native forest of Urucu presented similar microorganisms growth population with gasoline and diesel oil addition. The soil rhizosphere from cupuassu, camu-camu and arassa-boi presented better growth with gasoline, except graviola rhizosphere soil presented a better growth microorganisms population with diesel oil. All samples enriched with gasoline and diesel presented significant microorganisms growth population already at 7 days. All the soil samples enriched or/not with 1% of gasoline or diesel oil presented significant decreases of microbial population at 28 days of incubation. Key words: Theobroma grandiflorum, Annona muricata, Myrciaria dubia, Eugenia stipitata; bioremediation, petroleum biodegradation; Amazon.